Psykhe (Santiago) 2021
DOI: 10.7764/psykhe.2018.22185
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Mental Health: Mediation Effects of Coping Strategies in LGB and Heterosexual Youth

Abstract: Previous studies reveal that the negative effect of discrimination on mental health is particularly pernicious among stigmatised minorities. However, research also points out the importance of protection mechanisms that may buffer its effect. This study aimed to explore the relationships between mental health, perceived discrimination, and coping strategies of positive reframing and self-blame in LGB and heterosexual youth. Data were collected through a paper and pencil and an online survey administered to 195… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
2
1
Order By: Relevance
“…Moreover, Habarth et al (2019b) found that non-heterosexual women who endorsed normative behaviorcharacteristics found in Profile 3-reported lower psychological well-being (i.e., autonomy, growth, sense of purpose). Our findings do not support this evidence, but they align with a study with Portuguese high school students which showed that LGB and heterosexual participants had similar mental health levels (Fonseca de Freitas et al, 2021). Hence, besides heteronormative attitudes, factors related to culture, life period, and the COVID-19 pandemic may be operating in these mixed results regarding mental health.…”
Section: Heteronormativity and Well-being Indicatorscontrasting
confidence: 87%
“…Moreover, Habarth et al (2019b) found that non-heterosexual women who endorsed normative behaviorcharacteristics found in Profile 3-reported lower psychological well-being (i.e., autonomy, growth, sense of purpose). Our findings do not support this evidence, but they align with a study with Portuguese high school students which showed that LGB and heterosexual participants had similar mental health levels (Fonseca de Freitas et al, 2021). Hence, besides heteronormative attitudes, factors related to culture, life period, and the COVID-19 pandemic may be operating in these mixed results regarding mental health.…”
Section: Heteronormativity and Well-being Indicatorscontrasting
confidence: 87%
“…The demanding response to the partner is associated with coping strategies, because they are a set of skills to interact and resolve the various psychological or social situations of an internal or external nature, which are perceived as a threat to the subject, contain a cognitive and/or behavioral component (Barbé, 2023;Palet, 2023). Therefore, inadequate coping strategies explain why some young university students remain in violent relationships and involved in an affective-dependent style, affecting their psychological well-being and integrity (Momeñe et al, 2021;Villa & Gonzalez, 2019;Fonseca et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…People may attribute unfair treatment in their daily lives for a variety of reasons including but not limited to their weight or other aspects of physical appearance (Sutin et al, 2016); racialized group membership and ethnicity (Seaton et al, 2010; Unger, 2018); gender identity, gender expression, and sexual orientation (Wyman Battalen et al, 2021; Fonseca de Freitas et al, 2021); and socio-economic status (Jokela & Fuller-Rowell, 2022Jokela & Fuller‐Rowell, 2022). Yet, a person experiences these multiple social statuses and accompanying discrimination related to these statuses at the same time, not separately (Grollman, 2012).…”
Section: Introductionmentioning
confidence: 99%